Financial Information for Management of a Development Finance Institution : some guidelines - Mould, Maurice C. (Washington, D.C. : World Bank, 1987)
The primary objective of this two-part guideline is to encourage the demand for, and to advise on the generation and use of explicit accurate and timely financial information in Development Finance Institutions.
osc 12/06/2017
Loans
Keywords: Development credit corporations; Development banks